2014
DOI: 10.1371/journal.ppat.1004067
|View full text |Cite
|
Sign up to set email alerts
|

Prophenoloxidase Activation Is Required for Survival to Microbial Infections in Drosophila

Abstract: The melanization reaction is a major immune response in Arthropods and involves the rapid synthesis of melanin at the site of infection and injury. A key enzyme in the melanization process is phenoloxidase (PO), which catalyzes the oxidation of phenols to quinones, which subsequently polymerize into melanin. The Drosophila genome encodes three POs, which are primarily produced as zymogens or prophenoloxidases (PPO). Two of them, PPO1 and PPO2, are produced by crystal cells. Here we have generated flies carryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
274
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(287 citation statements)
references
References 57 publications
(109 reference statements)
12
274
1
Order By: Relevance
“…They play a key role in host defense through melanization and they participate in wound healing. Lamellocytes are large (15 to 40 m in diameter), flat adherent cells which encapsulate and neutralize objects too large to be phagocytosed by plasmatocytes (30)(31)(32). Of note, the question of the involvement of hemocytes in antiviral immunity has not been a focus of interest so far for Drosophila.…”
Section: Importancementioning
confidence: 99%
“…They play a key role in host defense through melanization and they participate in wound healing. Lamellocytes are large (15 to 40 m in diameter), flat adherent cells which encapsulate and neutralize objects too large to be phagocytosed by plasmatocytes (30)(31)(32). Of note, the question of the involvement of hemocytes in antiviral immunity has not been a focus of interest so far for Drosophila.…”
Section: Importancementioning
confidence: 99%
“…Enterococcus faecalis and Staphylococcus aureus have been used to probe the Toll pathway in survival experiments, and occasionally Aerococcus viridans has been used to stimulate a Toll-dependent immune response. S. aureus is especially interesting to probe the role of phagocytosis and melanization [22,23,131]. Among DAP-type Gram-positive bacteria, Listeria monocytogenes, Listeria innocua, Bacillus megaterium and Bacillus subtilis are currently being used (for example [24]).…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
“…The most historic is Black cells, a gain-of function mutation in PPO1 that affects both PPO1 and PPPO2 proteins ( [51], Neyen, unpublished observations). More recently, a double PPO1, PPO2 mutant was generated which shows complete absence of PO activity in the hemolymph [131].…”
Section: Immune Deficiency Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The melanization cascade, activated by the prophenoloxidase (proPO) system, has been documented as an important immune mechanism in shrimp and other arthropods in their defense against pathogens (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Most studies have shown that the melanization reaction is initiated by microbial elicitors, which then activate the proteolytic cascade that terminates with the activation of the zymogen proPO into the active phenoloxidase (PO) enzyme.…”
mentioning
confidence: 99%